Species richness and areas of endemism of oryzomyine rodents (Cricetidae, Sigmodontinae) in South America: an ndm / vndm approach - Joyce R. do Prado; Pamella G. G. Brennand; Leandro P. Godoy; Gustavo S. Libardi; Edson F. de Abreu‐Júnior; Paulo R. O. Roth; Elisandra A. Chiquito; Alexandre R. Percequillo (Journal of Biogeography, 2015)
Aim To infer areas of endemism for the tribe Oryzomyini in South America by employing a database of species richness and geographical distribution, and to compare these results with areas of endemism and species richness proposed in the literature for other taxa. Location We analysed specimens of the tribe Oryzomyini distributed throughout South and Central America, which are housed in European, North and South American museums and collections. Methods We analysed 2768 occurrence records for 102 species of the tribe Oryzomyini using the ndm / vndm algorithm and three different grid sizes to assess the possible effects of grid cell area on the results. Results Using the overlap of consensus areas in South America, we identified three generalized areas of endemism for the Oryzomyini: north‐western South America ( NWSA ), eastern South American ( ESA ), and northern South America ( NSA ); we also identified the Galápagos archipelago ( GA ) as an area of endemism. Main conclusions Areas of endemism detected in the continental portion of South America include its three main mountain chains: the Andes Cordillera, the Guyanan Shields, and an area east of the Brazilian Shield named Serra do Mar. Each of these regions encompasses many different types of vegetation, and the species richness and composition of the areas of endemism of the tribe are directly related to this environmental diversity. Different grid sizes affected the distributional heterogeneity of the consensus areas. The smallest grid cell size identified mainly Andean areas, which contain a higher number of more exclusive species in a small area along a steep elevational gradient. In contrast, the largest grid size identified areas of endemism along an environmental gradient that co‐varied with latitude and longitude. The identified areas of endemism are corroborated by previous studies on other taxa.